Hubungan Kecerdasan Linguistik dengan Kemampuan Semantik Anak Gangguan Neurodevelopmental di Sekolah Luar Biasa Kota Surakarta - Nuha, Amirah; Muryanti, Muryanti (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Background: Neurodevelopmental disorders are associated with disorders that lead to brain development characterized by an inability to reach normal limits of cognitive, emotional and motor development. This is also characterized by a delay in the language development process. Cognitive-linguistic is the ability to use language, both written and spoken, in various forms to express ideas. One of them is semantic skill. Semantics is the part of language structure that is related to the meaning of expressions and the meaning structure of speech. Objectives: This study aims to determine the relationship between cognitive-linguistic and semantic skill in children with neurodevelopmental disorders in special schools in Surakarta City. Methods: This research is a quantitative research with a descriptive correlational research design. The sampling technique used is purposive sampling with 60 respondents. The research instrument uses a linguistic intelligence test (Cognitive Linguistic Evaluation) and a semantic ability questionnaire. The statistical test used in this study is Kendall's Tau. Results: The results of the Kendall's Tau test showed a ρ value of 0.000 (ρ < 0.05) and a correlation strength of 0.417. This means that there is a relationship between cognitive-linguistic and semantic skill, with a moderate correlation strength and a positive correlation direction. This means that the higher the child's cognitive-linguistic, the higher their semantic skill. Conclusion: There is a relationship between cognitive-linguistic and semantic skill in children with neurodevelopmental disorders in special schools in Surakarta City. Keywords: Cognitive-Linguistic, Semantic, Neurodevelopmental Disorders